2012
DOI: 10.1111/jre.12019
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression of metalloproteinase‐8 and ‐13 and their relationships with extracellular matrix metalloproteinase inducer in the development of ligature‐induced periodontitis in rats

Abstract: The levels of expression of MMP-8 and MMP-13 are temporally varied at different periods during the development of experimental periodontitis. The level of expression of EMMPRIN is closely associated with the expression of MMP-13, but not with the expression of MMP-8. In addition, MMP-13 might be involved in alveolar bone destruction, as well as in physiological bone remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 37 publications
(78 reference statements)
5
29
0
Order By: Relevance
“…The number of osteoclasts was also found to peak on day 3, but there was still an exponential augment in alveolar bone loss from day 3 to day 11. The findings for osteoclasts and alveolar bone resorption in our research were in accordance with our studies and other research . The possible reasons for this phenomenon are as follows.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The number of osteoclasts was also found to peak on day 3, but there was still an exponential augment in alveolar bone loss from day 3 to day 11. The findings for osteoclasts and alveolar bone resorption in our research were in accordance with our studies and other research . The possible reasons for this phenomenon are as follows.…”
Section: Discussionsupporting
confidence: 82%
“…The rats were randomly allocated to six groups, namely one healthy control group (day 0) and five periodontitis groups (days 3, 5, 7, 11 and 15), with 10 rats in each group. Experimental periodontitis was set up in the periodontitis groups based on our published study . In short, the rats were deeply anesthetized with 10% chloral hydrate (3.33 mL/kg, intraperitoneal injection).…”
Section: Methodsmentioning
confidence: 99%
“…The retention of bacterial plaques caused by the ligatures can lead to inflammatory cell infiltration, attachment loss and bone loss, which were similar to human periodontitis . According to our previous studies, alveolar bone was significantly destroyed from day 0 to 7, and stabilized from day 11 to day 21 . Therefore, day 7 had been chosen to be the end day.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the tumor microenvironment, EMMPRIN on tumor cells stimulates the expression of several types of MMPs through crosstalk with fibroblasts . Our previous studies demonstrated that EMMPRIN and MMPs were up‐regulated in periodontal tissue from humans and rats with periodontitis compared with humans and rats with healthy periodontal tissue . However, the mechanism underlying the host immune‐inflammatory response mediated by different glycosylation forms of EMMPRIN in periodontitis development remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This process is regulated by multiple factors, leading to the different outcomes of the inflammatory response that are observed . As an inducer of MMPs, extracellular matrix metalloproteinase inducer (EMMPRIN) has been demonstrated to be overexpressed and to be associated with the overexpression of MMPs in periodontitis . Moreover, there are different glycosylated forms of EMMPRIN that have different abilities to activate MMPs …”
Section: Introductionmentioning
confidence: 99%